Stimulus of cross dispersion on Williamson liquid flow owing to stretched sheet with convective-diffusive situations (Journal of Naval Architecture and Marine Engineering, 2023)
The present research wishes to analyse the heat plus mass transmission features on magnetohydrodynamic stream of Williamson liquid owed to stretching surface with cross dispersion impacts. The stimulus of radiative heat, mutable heat sink/source, dissipation, Joule’s heat and chemical reaction is taken. With the support of similarities the original PDEs are transmuted into ODEs and then obtain a numerical solution by the well-known numerical method R.K. with shooting procedure. The stimulus of dissimilar dimentionless constraints on the flow fields are conversed over displays and the same parameters on skinfriction coefficient, local heat plus mass transport rates are deliberated through table. An improvement in thermal field is perceived for thermic heat constraint and Eckert number. On the other hand, it is witnessed that expanding the values of Dufour quantity enhances the distribution of heat, while a contrary outcome is noticed in the distribution of concentration.